2005
DOI: 10.1021/ic0500053
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Interactions in Unusual Backbone Nitrogen-Coordinated Zinc Peptide Complexes:  A Crystallographic and Spectroscopic Study

Abstract: A series of zinc complexes with dipeptide ligands of the type Dpg-Xaa was synthesized, where Dpg is dipicolylglycine and Xaa is phenylalanine (Phe), tyrosine (Tyr), tryptophan (Trp), 2-naphthylalanine (Nal), or glycine (Gly). It was shown that aromatic interactions promote the unusual coordination of an anionic peptide backbone nitrogen atom to zinc. This binding mode was, for the first time, characterized by X-ray structure analyses of the electrically neutral complexes [(Dpg-Phe)(-H)Zn], [(Dpg-Tyr)(-H)Zn], [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 70 publications
1
10
0
Order By: Relevance
“…This switching of the amide coordination mode has been to be fully reversible upon protonation with hydrochloric acid. [8] Similar pHdependent rearrangements have been reported by other groups for complexes with tripodal ligands featuring amine and amide donor groups. [9] Compared to their analogs with aromatic pyridyl donor groups, tripodal ligands with aliphatic amine groups have attracted much less attention.…”
Section: Introductionsupporting
confidence: 75%
“…This switching of the amide coordination mode has been to be fully reversible upon protonation with hydrochloric acid. [8] Similar pHdependent rearrangements have been reported by other groups for complexes with tripodal ligands featuring amine and amide donor groups. [9] Compared to their analogs with aromatic pyridyl donor groups, tripodal ligands with aliphatic amine groups have attracted much less attention.…”
Section: Introductionsupporting
confidence: 75%
“…We mutated these three histidine residues to the corresponding substitutions in human 14-3-3ζ (Figure S1), and prepared H158F-, H164E- and H195S-14-3-3γ. We also prepared the mutant Y117F, since the non-conserved Tyr117 π-stacks with His164 (Figure 4D) and might modulate the p K a -value of the histidine, as described in other systems [52]. The four mutants were purified at similar yields as wt-14-3-3γ and also showed similar affinity for binding the phosphopeptide THp-(1-43) as wt (Figure 2A and data not shown).…”
Section: Resultsmentioning
confidence: 83%
“…While the mimics of biological N 2 S 2 binding sites,i ncluding the ema ligand have been studied for decades,t his example of H 2 ema 2À as ab inucleating ligand is unknown or unreported until now.T he synthetic paths to complex 5 emphasize metal exchange processes in intricate proton/metal competitions that are likely related to synthetic routes to metalloproteins and enzymes.E ngagement of carboxamide oxygens as donor sites for zinc in peptide bioconjugates have been observed by the Alsfasser group, [16] while Hahn et al, have reported apHdependent, reversible switching of the N/ Oa mide coordination modes in tripodal complexes of Zn II , Cu II ,a nd Ni II . [17] More closely related to our discovery are well-designed studies via infrared multiple photon dissociation spectroscopy and DFT calculations from Dunbar et al, who explored the "basic tension" in small peptides between deprotonated amido nitrogens that bind to metals vs.t he tautomeric,carboxy bound form.…”
Section: Resultsmentioning
confidence: 92%